2006
DOI: 10.1111/j.1365-2141.2006.06312.x
|View full text |Cite
|
Sign up to set email alerts
|

Haematological malignancies developing in previously healthy individuals who received haematopoietic growth factors: report from the Research on Adverse Drug Events and Reports (RADAR) project

Abstract: Summary Pegylated recombinant human megakaryocyte growth and development factor (PEG‐rHuMGDF) and granulocyte colony‐stimulating factor (G‐CSF) promote haematopoietic progenitor cell maturation. We reviewed the findings for healthy volunteers/donors who developed haematological malignancies following PEG‐rHuMGDF or G‐CSF administration. Information was reviewed for three of 538 volunteers who received PEG‐rHuMGDF in clinical trials and two of 200 donors who underwent G‐CSF mobilised stem cell harvesting proced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
96
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(100 citation statements)
references
References 41 publications
3
96
1
Order By: Relevance
“…The few cases of acute myeloid leukemia reported in healthy donors, 3 are rather consistent with the age-adjusted incidence of leukemia in adults; 4 and in one case, offers some insights into the mechanisms of leukemogenesis. 5 Fortunately, G-CSF, at least in the unrelated donor setting remains listed under the IND protocols, which implies that every donor provides informed consent for the research, including agreement for perpetual annual follow-up.…”
supporting
confidence: 54%
“…The few cases of acute myeloid leukemia reported in healthy donors, 3 are rather consistent with the age-adjusted incidence of leukemia in adults; 4 and in one case, offers some insights into the mechanisms of leukemogenesis. 5 Fortunately, G-CSF, at least in the unrelated donor setting remains listed under the IND protocols, which implies that every donor provides informed consent for the research, including agreement for perpetual annual follow-up.…”
supporting
confidence: 54%
“…Reports on malignancies after rhG-CSF administration in healthy individuals are still anecdotal, and in most cases a genetic risk may be present as donors experienced the same malignant entity as their siblings. 9,11 In a small study, Nagler et al 34 observed epigenetic changes in lymphocytes of healthy individuals after rhG-CSF administration, which were similar to those seen in cancer patients. The compliance of donors for follow-up was rather low in our sibling donor population, probably because of residences being far away from the donation center or because of the death of the relatives for whom they donated.…”
Section: Table 2amentioning
confidence: 78%
“…Several donors were identified who experienced acute leukemia after rhG-CSF administration. 9,10 Bennett et al 11 reported two malignancies among 200 sibling donors within 5 years. An ongoing monitoring of risks, possibly associated with rhG-CSF administration to healthy donors, should be warranted.…”
Section: Introductionmentioning
confidence: 99%
“…A few cases of leukemia in PBSC donors have been reported, although these publications have been criticized for selection bias and misleading statistical techniques [19,48,49]. The National Marrow Donor program (NMDP) has recently provided some reassuring data on this issue.…”
Section: The Question Of Possible Long-term Adverse Eventsmentioning
confidence: 99%